New Plants for Florida: Introduction - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS, 2003)
New plants developed at the Florida Agricultural Experiment Station (FAES) have been vital to the state’s agricultural industries and to consumers here and throughout the country and the world. New crop varieties are developed through research led and conducted by plant breeders with cooperation from scientists in other agricultural disciplines. These varieties may have higher yield; they may be more resistant to pests, or they may be healthier for consumers. Almost every crop variety grown in Florida came from plant breeding programs at FAES. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.